PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN MOTIVASI BERWIRAUSAHA TERHADAP MINAT BERWIRAUSAHA DENGAN SELF EFFICACY SEBAGAI VARIABEL INTERVENING PADA SISWA SMK NEGERI 1 PATI - Sulistiowati, Linda Ayuk; Indaryani, Mamik; Wismar'ein, Dian (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2024)
ABSTRACTThis study aims to analyze the effect of entrepreneurship knowledge and entrepreneurial motivation on entrepreneurial interest with self-efficacy as an intervening variable in students of SMK Negeri 1 Pati. The population of this study amounted to 976 students and female students of SMK Negeri 1 Pati and the number of samples studied was 120 students using purposive sampling method, and the data were processed using AMOS 24. The results of this study indicate that there is a positive and significant influence between entrepreneurial knowledge variables on entrepreneurial interest. There is a negative but insignificant influence between entrepreneurial motivation variables on entrepreneurial interest. There is a positive and significant influence between self efficacy variables on entrepreneurial interest. There is a positive and significant influence between the variables of entrepreneurial knowledge and entrepreneurial motivation on self-efficacy. Keywords: Entrepreneurial knowledge, Entrepreneurial motivation, Entrepreneurial interest, Self Efficacy.